(untitled) (International Journal of Innovative Technologies in Economy, 2025)
This research aims to investigate the use of fundamental and technical analysis in analysing companies in Indonesia. Using data from some companies listed on the Indonesia Stock Exchange (IDX), this research analysing company performance and using both approaches to evaluate investment prospects. Fundamental analysis methods involve qualitative and quantitative assessments of a company’s performance, including the financial statements. On the other hand, technical analysis uses historical stock price data and trading volume to identify some trends, chart patterns, and other indicators. This will help some investors to identify the right moment to buy or sell stocks. This research contributes to the understanding of the use of fundamental and technical analysis in the Indonesian capital market. The findings from this research can be used by investors, financial analysts, and other stakeholders to make some better investment decisions and manage risk more effectively.